On the Archaeographic Project “Kharkiv University in the Memories of Its Faculty and Students, 1941‒1945” - Posokhov, Sergiy (The Journal of V. N. Karazin Kharkiv National University. Series History, 2024)
The report discusses a continuing series of archaeographic publications dedicated to Kharkiv University in the memories of members of its student body, faculty, and staff, focusing in particular on the fourth volume of the series, which deals with World War II, or more specifically with the period of 1941‒1945. The collection, published in 2023, includes various types of ego-documents: not only memoirs, but also diaries, letters, transcripts, and official autobiographies. The contents of the texts are also quite diverse, reflecting the often divergent life paths of the authors (some of them found themselves in emigration). Taken together, these writings create opportunities for factual comparison, help achieve a more complete and comprehensive understanding of the history of Kharkiv university during World War II, and illustrate the mechanisms of construction and functioning of historical memory.